Experimental Investigation of a Vacuum Cooling System - Zhang, Si Wei (2009)
The quality and safety of food are currently concerned by the world of population now. Usually, the surface temperature of horticultural crops, such as vegetables and fruits, remain high after harvesting. With the strong respiration, they continually release heat, so that the contented water keeps on evaporating and losing. Consequently, the deterioration will happen and get worse during this period. Therefore, several pre-cooling methods come up in succession, such as hydro-cooling, room cooling, forced air cooling and others. Apart from these methods, vacuum cooling is also an effective and a rapid evaporative pre-cooling method for porous and moisture foods to meet special cooling requirements. The basic principle of vacuum cooling consists of removing the latent heat of a product, which implies a rapid decrease in the temperature. Vacuum cooling can be used as an effective method for pre-cooling to prolong their shelf life or by preventing the influence of heat field. In previous research on this subject matter, the vacuum cooling method has been used in relation to food products. However, the cooling times from these research still has the challenge to improve. This could be due to the disposition of system equipment, the vacuum pump selection or the matching between pumping speed and chamber volume. None of the studies conducted so far has referred to vacuum pump selection and the matching between pumping speed and chamber volume. A proper research investigation on this selection and matching could benefit the vacuum cooling method to improve upon the cooling times. In this study, the selection of vacuum pump and the matching between pumping speed and chamber volume of vacuum cooling system are discussed and investigated in detail. A product of vacuum cooling system was designed without vapour condenser and operated by a single oil vacuum pump. Tests were carried out to investigate the effect of different vacuum levels, pumping speeds and temperatures on selected vegetables in the vacuum cooling process. Based on the discussion on the pressure, pumping speeds and temperatures, the results indicate that the vacuum cooling system can be operated without vapour condenser and by a single oil vacuum pump. The results also show that porous products pre-cooling using this method can be shortened in less than 4 min in this type of vacuum cooling system.